Exclusive Dakwah and Effective Branding: A Case Study of Majelis Taklim Zaadul Muslim in Examining Jamaah Loyalty Through the Touchpoint Method - Rachmad Anwar Nuris; Taufik Murtono (Dinasti Publisher, 2025)
This study examines the phenomenon of the high number of attendees at Majelis Taklim Zaadul Muslim, despite its exclusive and closed-content religious gatherings. This research is important to identify the factors that make this Majelis Taklim highly appealing and to understand how its unique strengths attract specific market segments. The objective of the study is to explain the dissemination of Majelis Taklim Zaadul Muslim's ideas through branding activities. The research employs a qualitative method, utilizing Talcott Parsons' cultural theory to explore participants' in-depth experiences. Alina Wheeler's brand touchpoint theory is used to identify the mediums that connect the attendees. Data were collected through in-depth interviews, participatory observations, and content analysis. The findings reveal that effective brand touchpoints contribute to the increasing number of attendees from diverse backgrounds. The main findings include: 1) The da'wah model of Habib Alwi As-Segaf, which adheres to Asy’ariyah and Maturidiyyah theology, 2) Branding activities that create emotional connections and a strong image, and 3) Positive perceptions of branding among attendees. This study recommends further research using an anthropological approach and can serve as a reference for new Majelis Taklim in implementing branding strategies in their da'wah activities.